The Islamophobia industry how the right manufactures fear of Muslims - Lean, Nathan Chapman; Esposito, John L. (London : Pluto Press, 2012)
This is a disturbing account of the rising tide of Islamophobia sweeping through the United States and Europe. Nathan Lean takes us through a world of conservative bloggers, right-wing talk show hosts, evangelical religious leaders and politicians, all united in their quest to exhume the ghosts of 9/11 and convince their compatriots that Islam is the enemy. Lean uncovers their scare tactics, reveals their motives and exposes the ideologies that drive their propaganda machine. Situating Islamophobia within a long history of national and international phobias, this book challenges the narrative of fear that has for too long dominated discussions about Muslims and Islam.
1. Monsters among us: a history of sowing fear in America -- 2. A web of deception: fomenting hate online -- 3. Media mayhem: broadcasting anti-Muslim madness -- 4. We come bearing crosses: the Christian Right's battle for eternity -- 5. Of politics and prophecy: the alliance of the pro-Israel right -- 6. To Washington and beyond: Islamophobia as government policy -- 7. Across the pond: the deadly effects of hate in Europe.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Islamophobia; Ethnic conflict; Islam -- Public opinion; Muslims -- Public opinion; Islam and politics; Muslims -- Non-Muslim countries; Islamic civilization; Civilization, Western; Intercultural communication; East and West; Islamic countries -- Relations -- Western countries; Western countries -- Relations -- Islamic countries; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Minority Studies; Electronic books